Amish Marketplace : The Farm Stand - Book 2 - Clipston, Amy (Grands Rapids, Michigan : Zondervan, 2020)
"Salina Petersheim runs her own booth at the Amish market, where shes known for having the freshest and most delicious produce in the area. Her father is the bishop of her church district, and her brother is a deacon. They are a very close family, yet sometimes she tires of being compared to her older brother, Neil, who is married and has two children. She also feels the pressure of having to be the perfect daughter for her parents. Salina has been dating Josiah for almost a year now, but he feels more like a friend than a boyfriend. Her parents approve of Josiah, who is a hardworking roofer. Hes handsome and easy to talk to, but he just doesnt warm her heart the way she feels a boyfriend and future husband should. She secretly longs for more. Along comes William Will Zimmerman, a Mennonite chef who runs a restaurant located next door to the Amish market. He wants Salina to supply the produce for his restaurant, and as they forge a business relationship, they both feel themselves falling in love. Salina especially tries to deny her feelings for Will since her father wants her to marry within the community. Both Salina and Will feel stuck in their current relationships, but they cannot deny what they feel for each other. Will they follow their hearts or bow to the pressure of family? Or will God provide a surprising new road for them?"
Keywords: Amish -- Fiction; Mennonites -- Fiction; Man-woman relationships -- Fiction; Brothers and sisters -- Fiction; Farmers markets -- Fiction; Christian fiction; Romance fiction; Religious fiction; Inspirational fiction